A multiperspective learning approach among Malaysian university students in the context of epistemological beliefs - Hassan, Aminuddin; Ismail, Habsah; Muhamad, Mohd Mokhtar; Wan Ali, Wan Zah; Konting, Mohd Majid (Universiti Putra Malaysia Press, 2012)
Students in higher education institutions, particularly in public and private universities in Malaysia share certain common epistemological beliefs among them, while other aspects of the beliefs are significantly different. The characteristics of students based on epistemological beliefs enlighten those who are responsible in academic and soft skill development of higher education on how to appreciate and utilize the talents and strength in each student. Their characteristics could be identified by observing the way they put on their perspective on the list of given scenarios in a survey questionnaire used in this research. These characteristics are identified from their responses to various constructs of epistemological beliefs and learning approaches used in this research. This move is in line with the intention of educationists and policy makers of higher education in Malaysia to dig up the potential among the country’s future leaders as much as possible. This is one of the efforts taken by the educationists and policy makers of higher education in Malaysia to uncover the potential of students at the higher education level for future leaders of the country, beginning with their beliefs in knowledge and their learning approaches. Generally, these students are very prospective human capital in this country who need be groomed continuously. Hence, as one of the sources of prospective human capital in this country which needs continuous grooming, there is a need to examine their learning approaches and their concepts of knowledge as conducted in this study. In answering the research questions, the following significant differences were established between the variables used in this study: significant relationship between students’ epistemological beliefs and their surface learning approaches; significant difference between male and female students’epistemological beliefs and learning approaches; significant difference